2019
DOI: 10.3390/chemosensors8010005
|View full text |Cite
|
Sign up to set email alerts
|

Screen Printed Electrode Based Detection Systems for the Antibiotic Amoxicillin in Aqueous Samples Utilising Molecularly Imprinted Polymers as Synthetic Receptors

Abstract: Molecularly Imprinted Polymers (MIPs) were synthesised for the selective detection of amoxicillin in aqueous samples. Different functional monomers were tested to determine the optimal composition via batch rebinding experiments. Two different sensor platforms were tested using the same MIP solution; one being bulk synthesized and surface modified Screen Printed Electrodes (SPEs) via drop casting the microparticles onto the electrode surface and the other being UV polymerized directly onto the SPE surface in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 30 publications
0
30
1
Order By: Relevance
“…It was noted, however, that the observed increase was smaller than expected based on previous measurements with MIPs and HTM, with an R th increase of 0.5 ºC/W obtained in the nM range 37 . One possible explanation was the total mass of polymer on the glass substrates.…”
Section: Thermal Measurementscontrasting
confidence: 67%
See 1 more Smart Citation
“…It was noted, however, that the observed increase was smaller than expected based on previous measurements with MIPs and HTM, with an R th increase of 0.5 ºC/W obtained in the nM range 37 . One possible explanation was the total mass of polymer on the glass substrates.…”
Section: Thermal Measurementscontrasting
confidence: 67%
“…Therefore, it would be highly expensive and inefficient to have a more complex fluorophore present in each site. We compare the performance of fluorescent MIPs in the form of 6 microparticles and thin films in terms of rebinding capacity 37 , and fluorescent response in the presence of the target. Within this analysis, we explore and optimise the procedure for producing MIPs as thin films in a reproducible and consistent manner.…”
mentioning
confidence: 99%
“…These results are, however, surprising when comparing the data to the literature, as research found on the development of MIPs towards amoxicillin suggests that acrylamide provides the better binding solution [ 42 ]. However, the two acrylamide based MIPs tested in the research outline performed extremely poor when compared to that of the MAA-based MIPs.…”
Section: Discussionmentioning
confidence: 94%
“…The component ratios used for the MIPs synthesized were based on previous literature regarding the monolithic polymerization of molecularly imprinted polymers [ 42 ]. In general, functional monomer (1.4 mmol), template (0.35 mmol), crosslinker (2.8 mmol), and DMSO (3.3 mL) were placed in a glass vial and dissolved O 2 purged from the mixture by bubbling N 2 through the solution for 30 s. AIBN (36.1 mg, 0.22 mmol) was then added to the resulting mixture, ensuring that the solution was thoroughly mixed before subjecting the solution to a UV lamp (BlueWave 200, wavelength: 300–450 nm), thus initiating polymerization under photochemical conditions.…”
Section: Methodsmentioning
confidence: 99%
“…For example, in 2015, researchers demonstrated the detection of tetracycline while using a simple triple helix molecular switch for the detection of tetracycline in tap water, achieving a detection limit of 2.09 nM [52]. In addition to tetracycline based antibiotics, aptamers and MIP based sensors have both been developed for other types of antibiotics, such as amoxicillin [53,54]. In the case of kanamycin, Geng et al even demonstrated the synergistic combination of MIPs and aptamers for the detection of kanamycin while using fluorescence quenching [55].…”
Section: Antibioticsmentioning
confidence: 99%